THE INFLUENCE OF WORKLOAD, WORK ETHIC AND EMPLOYEE LOYALTY ON THE PERFORMANCE OF EMPLOYEES OF THE DISASTER MANAGEMENT AGENCY OF THE SPECIAL REGION OF YOGYAKARTA - Julkifli; Subiyanto, Didik; Kirana, Kusuma Chandra (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to analyze the influence of workload on employee performance by considering the role of work ethic and employee loyalty at the Regional Disaster Management Agency (BPBD) of Yogyakarta City. A high workload can affect productivity and work quality, while work ethic and employee loyalty are seen as balancing factors in maintaining organizational performance. This study uses a quantitative approach with the type of associative research. The population in this study is all employees of BPBD Yogyakarta City totaling 60 people, with sampling techniques using the census method. Data collection was carried out through a closed questionnaire using the Likert scale, while data analysis was carried out by multiple linear regression using the SPSS version 25 program. The results showed that partially, workload had no significant effect on employee performance (p = 0.385 > 0.05), while work ethic (p = 0.001) and loyalty (p = 0.022) had a positive and significant effect on performance. Simultaneously, workload, work ethic, and loyalty had a significant effect on employee performance with an Adjusted R² value of 0.548, which means that the three variables explain 54.8% of employee performance variations. This finding confirms that the improvement in the performance of BPBD employees is more influenced by the development of work ethic and loyalty than by managing the workload alone. The practical implications of this study show the importance of managerial strategies in creating a balance of workload and strengthening the value of work ethic and loyalty to improve the effectiveness of public organization performance. Keywords: Workload, Work Ethic, Loyalty, Performance, BPBD Yogyakarta City